2002
DOI: 10.5588/09640569512940
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of tuberculosis in Kuwait from 1965 to 1999

Abstract: Tuberculosis in Kuwait declined steadily from 1965 to 1989. Since 1989 there has been a slight rise in TB incidence in Kuwait among both Kuwaiti nationals and non-nationals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Recent data from Kuwait, another Arabian country in the Persian Gulf region which also has a large expatriate population originating from TB endemic countries of South Asia and Southeast Asia, have also shown that the majority of isoniazid-resistant M. tuberculosis infections occur in the expatriate population [11,19]. Further, similar to the data reported here, most of the isoniazid-resistant M. tuberculosis strains from Kuwait also exhibited unique patterns in typing studies [5,11].…”
Section: Discussionsupporting
confidence: 73%
“…Recent data from Kuwait, another Arabian country in the Persian Gulf region which also has a large expatriate population originating from TB endemic countries of South Asia and Southeast Asia, have also shown that the majority of isoniazid-resistant M. tuberculosis infections occur in the expatriate population [11,19]. Further, similar to the data reported here, most of the isoniazid-resistant M. tuberculosis strains from Kuwait also exhibited unique patterns in typing studies [5,11].…”
Section: Discussionsupporting
confidence: 73%
“…Kuwait, an Arabian country in the Persian Gulf region with nearly 25 cases per 100 000 population, has a low incidence of TB [23]. However, Kuwait has a large expatriate workforce originating from TB endemic countries.…”
Section: Introductionmentioning
confidence: 98%
“…The recent estimates suggest that about one third of the world population is infected with Mycobacterium tuberculosis , 8-10 million people develop active disease and 2 million people die of TB each year [1] . In addition to being an international problem, TB is also a serious infectious disease problem in the countries of the Gulf Region, including Kuwait [2] . The effective control of TB is dependent on the availability of universally effi cacious vaccines and reagents for specifi c diagnosis [3] .…”
Section: Introductionmentioning
confidence: 99%